Evaluation of anxiety-like behaviors following ethanol withdrawal in mice: effects of cannabidiol - Letícia Pin Coltri; Vivian Tacyani Bonassoli; Humberto Milani; Rúbia Maria Weffort de Oliveira (Universidade Estadual de Maringá, 2020)
The abrupt interruption of ethanol consumption increases anxiety-like behaviors in rodents and may reflect different aspects of ethanol dependence in humans. Measuring emotional behaviors resulting from ethanol withdrawal may aid in testing potential pharmacological agents for the treatment of ethanol dependence. In the present study, we used forced expositon to ethanol 20% during 10 days to mice, followed by abrupt withdrawal of the substance. The animals were evaluated 7, 24 and 35 h after ethanol withdrawal in three different behavioral paradigms, i.e., the open field (OF), light dark (LD) transition and elevated plus maze (EPM), tests usually used to measure anxiety-like behaviors. This was done with the aim of identifying the best interval as well as the most appropriate behavioral test to detect the effects of drugs that can relieve anxiety induced by ethanol withdrawal in mice. We also evaluated the effect of cannabidiol (CBD 10, 30 and 60 mg/kg) in ethanol withdrawn mice because it has been shown to alliviate drug addicton and present anti-anxiety effects. Our results show significant behavioral changes at 24 h following ethanol withdrawal. Diazepam (4 mg/kg), used as a positive control, counteracted the effects of ethanol withdrawal in OF, LD box and EPM. Cannabidiol attenuated anxiety-like behavior produced at 24 h after abstinence from ethanol exposure only in the EPM test.